Konsep Kebebasan dalam Filsafat Islam Perspektif Al-Farabi dan Ibn Rushd - Fery Hidayat, Yogi (Tamadduna: Jurnal Peradaban, 2024)
This study aims to explore the concept of freedom in the thought of al-Farabi and Ibn Rushd, two great figures in the history of Islamic philosophy. The method used in this research is literature study by analyzing the works of al-Farabi and Ibn Rushd related to the concept of freedom. This study also compares and contrasts the views of the two philosophers on the concept of freedom. The results of the study show that al-Farabi and Ibn Rushd have different perspectives on the concept of freedom. For al-Farabi, freedom is a concept related to individual and overall societal happiness. While for Ibn Rushd, freedom is related to the ability of individuals to think and act freely without limitations. This study also found similarities in the views of al-Farabi and Ibn Rushd on the concept of freedom. Furthermore, this research shows that the concept of freedom in the thought of both philosophers can be applied in the context of modern society to achieve justice and prosperity.